A NEW INTERNATIONAL ECONOMIC ORDER – 50 YEARS LATER (1974-2024) - FLORIN BONCIU (Global Economic Observer)
As 2024 marks 50 years of discussions and manifestations related to a New International Economic Order, and also 34 years since President George H.W. Bush presented his vision of a New World Order, this paper attempts to identify the main stages that characterized this important part of international relations. From an International Economic Order defined mainly by the Anglo-Saxon vision after the Second World War, new principles were proposed in 1974 as result of the demise of the colonial system and other changes in the world balance of power. For several decades these principles had little success, but currently the raise of new centers of power and the manifestation of a so-called Global South may determine a more substantial discussion about a New International Economic Order. The conclusions of this analysis aim to clarify the past and attempt to explore the future in order to provide a more efficient participation to international economic relations.